Effects of a ball-burnishing process assisted by vibrations in G10380 steel specimens. Issue 9 (December 2015) - Travieso-Rodriguez, Jose; Gomez-Gras, Giovanni; Dessein, Gilles; Carrillo, Francisco; Alexis, Joël; Jorba-Peiro, Jordi; Aubazac, Nathalie
Abstract This paper explores the effects on the surface roughness, hardness and residual stress of G10380 steel specimens milled and treated with a ball-burnishing process assisted by vibrations. These vibrations are incorporated through the attachment of an induced coil module to a conventional burnishing tool, with forces transmitted through a pre-loaded spring. A positive effect of vibrations on the improvement and efficiency of the burnishing treatment is demonstrated, empirically proving that the vibrations introduce additional energy into the system that aids with displacements along the surface of the material to reallocate the crystalline structure. Significant results are found in terms of final surface roughness, which is highly improved in comparison to conventional burnishing treatments, even with fewer passes and a significant time reduction. Less robust results are observed in terms of specimen hardness and residual stress, but future improvements could be derived with a thorough development of the vibration system.